Adherence to Disease Modifying Drugs among Patients with Multiple Sclerosis in Germany: A Retrospective Cohort Study - Hansen, Kerstin (PLoS One, 2015)
BACKGROUND: Long-term therapies such as disease modifying therapy for Multiple Sclerosis (MS) demand high levels of medication adherence in order to reach acceptable outcomes. The objective of this study was to describe adherence to four disease modifying drugs (DMDs) among statutorily insured patients within two years following treatment initiation. These drugs were interferon beta-1a i.m. (Avonex), interferon beta-1a s.c. (Rebif), interferon beta-1b s.c. (Betaferon) and glatiramer acetate s.c. (Copaxone). METHODS: This retrospective cohort study used pharmacy claims data from the data warehouse of the German Institute for Drug Use Evaluation (DAPI) from 2001 through 2009. New or renewed DMD prescriptions in the years 2002 to 2006 were identified and adherence was estimated during 730 days of follow-up by analyzing the medication possession ratio (MPR) as proxy for compliance and persistence defined as number of days from initiation of DMD therapy until discontinuation or interruption. FINDINGS: A total of 52,516 medication profiles or therapy cycles (11,891 Avonex, 14,060 Betaferon, 12,353 Copaxone and 14,212 Rebif) from 50,057 patients were included into the analysis. Among the 4 cohorts, no clinically relevant differences were found in available covariates. The Medication Possession Ratio (MPR) measured overall compliance, which was 39.9% with a threshold MPR≥0.8. There were small differences in the proportion of therapy cycles during which a patient was compliant for the following medications: Avonex (42.8%), Betaferon (40.6%), Rebif (39.2%), and Copaxone (37%). Overall persistence was 32.3% at the end of the 24 months observation period, i.e. during only one third of all included therapy cycles patients did not discontinue or interrupt DMD therapy. There were also small differences in the proportion of therapy cycles during which a patient was persistent as follows: Avonex (34.2%), Betaferon (33.4%), Rebif (31.7%) and Copaxone (29.8%). CONCLUSIONS: Two years after initiating MS-modifying therapy, only 30–40% of patients were adherent to DMDs.